Enzalutamide-induced and PTH1R-mediated TGFBR2 degradation in osteoblasts confers resistance in prostate cancer bone metastases. (28th January 2022) - Su, Shang; Cao, Jingchen; Meng, Xiangqi; Liu, Ruihua; Vander Ark, Alexandra; Woodford, Erica; Zhang, Reian; Stiver, Isabelle; Zhang, Xiaotun; Madaj, Zachary B.; Bowman, Megan J.; Wu, Yingying; et al.
Abstract: Enzalutamide resistance has been observed in approximately 50% of patients with prostate cancer (PCa) bone metastases. Therefore, there is an urgent need to investigate the mechanisms and develop strategies to overcome resistance. We observed enzalutamide resistance in bone lesion development induced by PCa cells in mouse models. We found that the bone microenvironment was indispensable for enzalutamide resistance because enzalutamide significantly inhibited the growth of subcutaneous C4–2B tumors and the proliferation of C4–2B cells isolated from the bone lesions, and the resistance was recapitulated only when C4–2B cells were co-cultured with osteoblasts. In revealing how osteoblasts contribute to enzalutamide resistance, we found that enzalutamide decreased TGFBR2 protein expression in osteoblasts, which was supported by clinical data. This decrease was possibly through PTH1R-mediated endocytosis. We showed that PTH1R blockade rescued enzalutamide-mediated decrease in TGFBR2 levels and enzalutamide responses in C4–2B cells that were co-cultured with osteoblasts. This is the first study to reveal the contribution of the bone microenvironment to enzalutamide resistance and identify PTH1R as a feasible target to overcome the resistance in PCa bone metastases. Highlights: Enzalutamide resistance is observed in PCa bone metastases. Enzalutamide-induced TGFBR2 decrease in osteoblasts contributes to drug resistance in PCa bone metastases. TGFBR2 decrease in osteoblasts is possibly through PTH1R-mediated endocytosis. Blocking PTH1R potentially overcomes enzalutamide resistance in PCa bone metastases.